The informativeness of earnings and management's issuance of earnings forecasts - Lennox, Clive S.; Park, Chul W. (Journal of Accounting and Economics, 2006)
Theory suggests that managers issue earnings forecasts to reduce information asymmetry. An earnings forecast is more effective in reducing information asymmetry if it contains earnings news that is relatively more informative about the firm's value. We hypothesize that a manager is more likely to issue an earnings forecast if investors perceive that earnings are more informative. We measure earnings informativeness by estimating the firm's earnings response coefficient (ERC) in quarters prior to the forecast issuance decision. Consistent with our hypothesis, we find that the firm's historic ERC is positively associated with management's issuance of earnings forecasts.